2022
DOI: 10.1002/cm.21713
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of kinesins in the pollen tube 30 years later

Abstract: The pollen tube is fundamental in the reproduction of seed plants. Particularly in angiosperms, we now have much information about how it grows, how it senses extracellular signals, and how it converts them into a directional growth mechanism. The expansion of the pollen tube is also related to dynamic cytoplasmic processes based on the cytoskeleton (such as polymerization/depolymerization of microtubules and actin filaments) or motor activity along with the two cytoskeletal systems and is dependent on motor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Notably, a decline in the number of functional proteins, particularly those involved in cytoskeletal organization, was previously also shown in mature HS tomato ( Solanum lycopersicum ) pollen ( Keller et al 2018 ). While transport of sperm cells and vesicles in pollen tubes is largely actin-dependent, microtubules and their kinesin motors play among others an important role of linking the sperm cells with the vegetative nucleus forming the MGU ( McCue et al 2011 ; Cai 2022 ). Their misexpression can well explain the observed transport defect.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a decline in the number of functional proteins, particularly those involved in cytoskeletal organization, was previously also shown in mature HS tomato ( Solanum lycopersicum ) pollen ( Keller et al 2018 ). While transport of sperm cells and vesicles in pollen tubes is largely actin-dependent, microtubules and their kinesin motors play among others an important role of linking the sperm cells with the vegetative nucleus forming the MGU ( McCue et al 2011 ; Cai 2022 ). Their misexpression can well explain the observed transport defect.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a decline in the number of functional proteins, particularly those involved in cytoskeletal organization was previously also shown in mature HS tomato pollen (Keller et al, 2018). While transport of sperm cells and vesicles in pollen tubes is largely actin-dependent, microtubules and their kinesin motors play among others an important role of linking the sperm cells with the vegetative nucleus forming the male germ unit (McCue et al, 2011; Cai, 2022). Their mis-expression can well explain the observed transport defect.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining analysis of tubulins and the GFP-tagged plus-end binding protein AtEB1 showed that pollen tubes contain longitudinally aligned microtubules in the shank region and shorter cables in the subapical region (Cheung et al, 2008; Cai and Cresti, 2010). Kinesins with the calponin homology domain (KCH), which belong to the kinesin 14 subfamily expressed in pollen tubes, are candidates for motor proteins that drive SCs, in a “tug-of-war” model (Cai et al, 1997; Schattner et al 2021; Cai, 2022). In vitro experiments have demonstrated that rice Os KCH1 interacts with both microtubules and actin fibers to drive fast (average 69.17 ± 14.77 nm s −1 ) and slow (average 24.2 ± 13.42 nm s −1 ) sliding movements (Schattner et al, 2021; Walter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%